Buddhist Principles in Business Promoting of the Nan Municipality Women’s Truth Saving Fund, Nan Province - Patsaman, Sichawat; Unsaun, Sittichai; Kamsom, Chuthamat (Journal of Thammawat, 2024)
The purpose of this article were: 1) to study the history of Nan municipality women’s truth saving fund, Nan province, 2) to study the management model of Nan municipality women’s truth saving fund, Nan Province, and 3) to study Buddhist principles for enhancing the procedure of Nan municipality women’s truth saving fund, Nan Province. This was a qualitative research with members of women’s truth saving fund providing important information using a purposive selection method. The result of the research found that Nan municipality women’s truth saving fund, Nan province has established in 2546 B.E. It was a grouping of women in the Nan municipality area. This fund had established to solve the lack of fund problem; giving women in Nan municipality bring the funds to use with effort, honesty, thrifty, and validity. The management models of Nan municipality women’s truth saving fund had two models, the original model depends on honesty and trust in the saving truth working group and the new model depends on a new management system that had 7 topics, there were planning, organizing, staffing, directing, Co-coordinating, reporting, and budgeting. Buddhist principles used for managing Nan municipality women’s truth saving fund are Brahmavihara 4, Iddhippada 4, Garavasadhamma 4, and Kalyanamittadhamma 7. Buddhist principles above could apply to develop and bring more morals in the working process, causing administrators and members have working with morals and more believable by making honesty in the working process bringing the development of fund increased, this could bring benefit from interest and dividend from the fund to create benefits for their own and community for sustainable development.